Implementation of Family Planning Village Program on the Effectiveness of Acceptor Users in Manjapai Village, Gowa Regency - Nurinzana, Nurinzana; Raodhah, Sitti; Rusmin, Muhammad (Public Health Science & Religion, 2023)
Background. The village family planning program is one of the government's innovative programs to reduce fertility rates in order to achieve balanced population growth, increase family resilience and welfare, prepare and regulate marriage and pregnancy, control birth rates and reduce maternal and child mortality after childbirth. The purpose of this study was to determine the implementation of the village family planning program in Kaluarrang Hamlet, Manjapai Village, Bontonompo District, Gowa Regency. Methods. This type of research is qualitative with a case study approach. Collecting data using interview and documentation techniques with a total sample of 13 respondents. The data collected from this study were sourced from primary data and secondary data. Results. The research results obtained are: (1) Communication in the implementation of the Kampung KB program so far can be said to have been implemented but has not been running effectively (2) The available resources are sufficient for both human, financial and budgetary resources originating from the APBN (3 ) Disposition related to the attitude of the implementer is not optimal due to lack of awareness and commitment in implementing this KB village program (4) The bureaucratic structure from the results of this study shows that the formation of the KB Village management has been carried out based on the SOP at the time of the declaration of formation in the KB Village. Conclusion. This study found that it is necessary to improve communication from the dimensions of consistency, clarity of information and transparency between implementors and target groups as well as monitoring in the implementation of Kampung KB program policies.